Estimation of the CTOD-crack growth curves in SENT specimens using the eXtended finite element method. (January 2019) - Ameli, Iman; Asgarian, Behrouz; Lin, Meng; Agbo, Sylvester; Cheng, Roger; Duan, Da-ming; Adeeb, Samer
Abstract: The single edge notched tension (SENT) test is commonly used to evaluate the less-conservative fracture toughness of pipeline steels. The R-curve (crack tip opening displacement (CTOD)-crack growth) behavior measured by SENT tests is similar to that measured during full-scale tests. This paper compares the ductile fracture mechanism of X42 grade steel, including crack initiation and propagation, using the extended finite element method (XFEM) with experimental data obtained from SENT tests. Two major parameters in XFEM (maximum principal stress and fracture energy) were calibrated in numerical models using experimental results obtained from SENT tests performed on six X42 grade steel samples to provide a CTOD-crack growth curve. With appropriate values of maximum principal stress and fracture energy, the numerical models can reasonably reproduce the experimental results. This method could be used to anticipate full-scale test behavior and simulate crack propagation in pipelines under operational loading conditions.